Insecticidal efficiency of plant essential oil nanoemulsion formulas against Spodoptera exigua - Passara, H.; Pumnuan, J.; Thongsaiklaing, T.; Thipmanee, K. (My University, 2024)
The findings revealed that the nEO formula of I. verum and C. longa demonstrated optimal effectiveness, with a concentration of 0.35% resulting in the highest mortality rate of 43.3%, 100% antifeedant effect and 85.0% growth inhibition activities in pupae. Additionally, a concentration of 0.25% led to 100% growth inhibition activities in adults. Consequently, the nEO formulas of I. verum and C. longa promise for the future development of botanical insecticides targeting the control of S. exigua.
Keywords: Antifeedant; Growth inhibition; Mortality; Nanoemulsion; Spodoptera exigua